Phytochemistry of Camellia sinensis or green tea: an update - Falcón-Guerrero , Britto Ebert (2024)
Green tea, or Camellia sinensis, is a type of unfermented tea that contains natural substances found in fresh leaves. It is considered the second most popular drink in the world after water. This review extensively examines the phytochemistry of green tea, as it exhibits antioxidant, anticancer, hypoglycemic, antibacterial, antiviral and neuroprotective pharmacological activities. Consequently, green tea has demonstrated promising practical applications for healthcare and disease prevention. To accomplish this, a search was conducted using bibliographic databases such as PubMed, Cochrane, and Web of Science to find articles related to the phytochemistry of green tea published between 2018 and 2023, in order to ascertain, with evidence, the properties of green tea.